Analyzing Employee Engagement in Business Community Case Study: Cimahi Creative Association - Fernando A, Jaka; Chaerudin, Rendra (Journal of Business and Management, 2015)
Abstract. The research aimed to know the current condition of employee engagement in Cimahi Creative Association, The methodology used is Questionnaire and Interview. Primary data is collected by questionnaires and interview that distributed to 100 employee and interview the Members of Cimahi Creative Association. Model approach in this study is done by constructing a new construct by combining several existing models, that is the Development Dimensions International (DDI), Employee Engagement and The Institute of Employment (IES) engagement models, and Ontario Hospital Association Model Employee Experience Survey (EES OHA ). Based on the purpose of the study is to describe the Employee Engagement in Cimahi Creative Association, the research method used is descriptive method. For measuring the level of employee engagement, researchers used a quantitative method through a questionnaire containing 46 questions and distributed to 100 respondents. After doing research, finally it was concluded that the highest dimension that most influence on employee engagement in the CCA is Interpersonal Support, and the lowest is the Individual values, as well as the highest indicator that led to employee engagement is a Family Friendliness, and the lowest is the pay Benefit and Payment. After averaged, generally members of the CCA has been engage towards the organizationÂ Keywords : Cimahi Creative AssociationEmployee engagement,Employee engagement Model, Business CommunityCategory: Individual Management, Human Resources Management, Employee Engagement